Animal models of Graves' disease and Graves' orbitopathy. Issue 5 (October 2015) - Nagayama, Yuji; Nakahara, Mami; Abiru, Norio
<x xml:space="preserve">Abstract</x> Purpose of review The purpose of this article is to summarize the recent advances on experimental Graves' hyperthyroidism and orbitopathy as studied in two widely used mouse models, which involve repetitive genetic vaccinations using either adenovirus or in-vivo electroporation of the eukaryotic expression plasmid expressing the thyrotropin receptor (TSHR) as a vector. Recent findings The models have been improved by using different types of antigens, including the holo receptor, the receptor A-subunit, an alternatively spliced form of variant receptor lacking a single leucine-rich repeat in the codomain, the receptors of human or mouse origin; different mice such as wild-type, TSHR knockout, TSHR transgenic and different inbred mice; and different immunization protocols. They are now useful for elucidating the pathogenic mechanisms of not only Graves' hyperthyroidism but also Graves' orbitopathy. Summary This review summarizes the literature of mouse models of Graves' hyperthyroidism and orbitopathy published over the last 3 years.